2020
DOI: 10.5530/ijmedph.2020.4.45
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Forms of Bullying Perpetration and Victimization in Indian Adolescents

Abstract: Background: Bullying in childhood and adolescence has pervasive negative impacts in adulthood in both victims and bullies. There are few studies describing the prevalence of bullying in Indian schools, and few which have documented the various forms of bullying prevalent in our country. This study is being carried out with working hypothesis that various forms of bullying perpetration and victimisation exists in Indian urban schools. Objectives: To study the prevalence of bullying perpetration/ victimization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…All 34 included cross-sectional studies reported the twelve-month prevalence of at least one type of violent communication (or had sufficient data for calculation). Among the 34 studies, 17 reported the overall prevalence of violent communication [ 9 , 30 , 37 , 38 , 39 , 40 , 41 , 43 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], 11 reported the prevalence of verbal and non-verbal violence separately without reporting the combined prevalence [ 8 , 31 , 36 , 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], 2 reported the prevalence of verbal violence only [ 32 , 68 ], and 4 reported the prevalence of non-verbal violence only [ 20 , 33 , 69 , 70 ]. Most studies saw verbal violence as the most common form of violent communication [ 31 , 36 , 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All 34 included cross-sectional studies reported the twelve-month prevalence of at least one type of violent communication (or had sufficient data for calculation). Among the 34 studies, 17 reported the overall prevalence of violent communication [ 9 , 30 , 37 , 38 , 39 , 40 , 41 , 43 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], 11 reported the prevalence of verbal and non-verbal violence separately without reporting the combined prevalence [ 8 , 31 , 36 , 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], 2 reported the prevalence of verbal violence only [ 32 , 68 ], and 4 reported the prevalence of non-verbal violence only [ 20 , 33 , 69 , 70 ]. Most studies saw verbal violence as the most common form of violent communication [ 31 , 36 , 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 34 studies, 17 reported the overall prevalence of violent communication [ 9 , 30 , 37 , 38 , 39 , 40 , 41 , 43 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], 11 reported the prevalence of verbal and non-verbal violence separately without reporting the combined prevalence [ 8 , 31 , 36 , 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], 2 reported the prevalence of verbal violence only [ 32 , 68 ], and 4 reported the prevalence of non-verbal violence only [ 20 , 33 , 69 , 70 ]. Most studies saw verbal violence as the most common form of violent communication [ 31 , 36 , 42 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The operational definition of violence varied across studies, with some of the studies referring to the standard definitions given by the International Labour Office (ILO) and/or World Health Organisation (WHO) [ 32 , 41 , 55 , 58 , 65 , 68 , 70 ], whereas few other studies had context-specific conceptualisations of violence based on the formative researches conducted by the respective authors on a similar sample prior to the assessment of prevalence [ 31 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations